Upconversion luminescence study of Er3+in Gadolinium-Calcium-Silicoborate glasses - Jakrapong Kaewkhao (2018)
The new glass series were prepared in compositions 25Gd 2 O 3 -10CaO-10SiO 2 -(55-x) B 2 O 3 -xEr 2 O 3 (where x is 0.0, 0.5, 1.0, 1.5, 2.0 and 2.5 mol %) by normal melt-quenching technique at the melting temperature of 1,400 °C. The optical spectra were measured and shown absorption bands were assigned to appropriate f-f electronic transitions of Er 3+ ions from the 4 I 15/2 ground state to the following excited states: 4 G 11/2 , 2 H 9/2 , 4 5/2 , 4 F 7/2 , 2 H 11/2 , 4 S 3/2 , 4 F 9/2 , 4 I 9/2 and 4 I 11/2 . Single peak from upconversion luminescence was observed at 531 nm (green) is assigned to the 2 H 11/2 → 4 I 15/2 . In this work, the strongest peak at 2.0% mol of Er 2 O 3 was observed. In this work, suggests that the Er 3+ ion in gadolinium calcium silicoborate glasses possibly considered as a potential candidate for applications in upconversion-based optical devices. © (2013) Trans Tech Publications, Switzerland.